118k views
4 votes
Can anyone help me with these two problems? Thank you.

Can anyone help me with these two problems? Thank you.-example-1
User Liong
by
5.5k points

1 Answer

4 votes


(\cos^4t-\sin^4t)/(\sin^2t)=\frac{(\boxed{\cos^2t}+\sin^2t)(\cos^2t-\sin^2t)}{\sin^2t}

which follows from the difference-of-squares identity,
a^2-b^2=(a+b)(a-b), with
a=\cos^2t and
b=\sin^2t.


=\frac{(\boxed{1})(\cos^2t-\sin^2t)}{\sin^2t}

which is due to the Pythagorean identity.


=\frac{\boxed{\cos^2t}}{\sin^2t}-(\sin^2t)/(\sin^2t)

by the distributive property;
1(\cos^2t-\sin^2t)=\cos^2t-\sin^2t.


=\cot^2t-1

by definition of cotangent,
\cot t=(\cos t)/(\sin t).


(\cos^2\theta)/(1-\sin\theta)=\frac{1-\boxed{\sin^2\theta}}{1-\sin\theta}

due to the Pythagorean identity.


=\frac{(1-\boxed{\sin\theta})(1+\sin\theta)}{1-\sin\theta}

by factorization of the numerator as a difference of squares.


=1+\sin\theta

by cancellation of
1-\sin\theta (provided
1-\sin\theta\\eq0).

User Ayman El Temsahi
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.